Immunoreactivity parameters in cardiosurgery patients - A. A. Silaev; E. P. Turmova; V. V. Volkov; E. V. Markelova; D. B. Andreev (Российский кардиологический журнал, 2005)
In 51 patients, immune status was assessed before and after coronary aortic bypass graft (CABG) surgery. All participants were divided into two groups: Group I - without any post-surgery complications (n=23; 45,5%); Group II - with post-surgery infectious and inflammatory pathology (n=28, 54,5%). Cardiosurgery patients had immunocompetent cell distribution pathology, which reflected immunity status abnormalities. Functional cell activity was decreased, humoral immunity was disturbed. In patients with septic complications, these disturbances were observed before CABG, and after the intervention they were even more severe. Immune disturbances in cardiosurgery patients play an important part in post-operative complications' pathogenesis, and ask for active risk factor screening, as well as for preventive immunotropic therapy.